"Lublin Triangle": Prospects for the Formation of a Transport and Logistics Cluster (Aspects of Modern Marketing Management) - Chebotarov, Ie. (Економічний вісник Донбасу, 2021)
The generalizing analysis of modern pan-European disintegration tendencies, especially against the background of forecasted such new tendencies, necessitates the search for other determinants of reliable international cooperation and the formation of stable international organizations. The new Lublin Triangle platform, consisting of Poland, Lithuania and Ukraine, which was founded in 2020, could be one of the few international organizations. The greatest economic effect and a number of concomitant institutional advantages of cooperation between these countries can give in the transport and logistics sphere with the formation of the transport and logistics cluster "Lublin Triangle". Taking into account a number of institutional and technical-functional factors, Latvia and Estonia can also be full participants in the proposed cluster; in this case, the proposed cluster may be called, for example, the Baltic-Eastern European Transport and Logistics Cluster. The categorical definition of the definition of "transport and logistics cluster" is substantiated. It is a set of spatially defined entities of all types of transport, infrastructure of their modes of transport and engineering industries, as well as related enterprises, institutions and governing bodies, which operates on the basis of a network of hubs. . The innovative nature of the proposal is that in contrast to the existing approaches in domestic and foreign science, according to which transport and logistics clusters are considered only within certain regions of a country, in this case: the understanding of the cluster , provisions and procedures of the Trans-European Transport Network (TEN-T) policy on the basis of modern marketing management; the cluster itself is offered in the form of appropriate transport and logistics hubs. The article, in addition to identifying the definition of "transport and logistics cluster" highlights the parameters of the proposed cluster with the disclosure of their content; cluster functions are classified; the structure of the network of geographical location of hubs is given.